Self-Efficacy Training Produces Significant Career Decision Changes in High School Students: Pelatihan Efikasi Diri Menghasilkan Perubahan Signifikan dalam Pengambilan Keputusan Karier pada Siswa Sekolah Menengah Atas - Adam Bagaskara; Effy Wardati Maryam (Academia Open, 2025)
General Background: Career planning during adolescence represents a critical developmental task requiring students to determine future educational and occupational pathways. Specific Background: High school students frequently experience uncertainty regarding post-graduation options due to limited knowledge of career pathways, parental expectations, and low confidence in evaluating personal abilities. Knowledge Gap: Although self-efficacy is widely recognized as a factor related to vocational decision processes, empirical evidence examining structured training programs designed to develop self-efficacy among Indonesian high school students remains limited. Aims: This study aimed to examine changes in career decision outcomes following self-efficacy training among grade XII students. Results: Using a quantitative quasi-experimental pre-post design, data were collected from 86 students at SMA Islam Sidoarjo using the adapted Career Decision Scale. Statistical analysis using the Wilcoxon signed-rank test demonstrated statistically significant differences between pre-test and post-test scores (p < .001), with median scores increasing from 43.00 to 45.00 and a large effect size (rank-biserial correlation = 0.489). The findings indicate increased confidence and improved readiness in determining future vocational plans after training implementation. Novelty: This study provides empirical evidence demonstrating measurable changes in vocational decision readiness through a structured self-efficacy training intervention within Indonesian secondary education settings. Implications: The findings support the integration of self-efficacy training into school-based career guidance programs to assist students in reducing uncertainty and strengthening preparedness for post-secondary academic or employment pathways. Highlights: Pre-Test and Post-Test Scores Demonstrated Statistically Verified Improvement in Vocational Readiness Levels. Wilcoxon Analysis Confirmed Strong Magnitude of Change Following the Intervention. Participants Demonstrated Greater Confidence and Reduced Hesitation in Selecting Future Pathways. Keywords: Self-Efficacy Training, Career Decision Making, High School Students, Quasi-Experimental Study, Career Decision Scale